Synthetic Biology Analysed Tools for Discussion and Evaluation - Engelhard, Margret (Ethics of Science and Technology Assessment, 2016)
Synthetic biology is a dynamic, young, ambitious, attractive, and heterogeneous scientific discipline. It is constantly developing and changing, which makes societal evaluation of this emerging new science a challenging task, prone to misunderstandings. Synthetic biology is difficult to capture, and confusion arises not only regarding which part of synthetic biology the discussion is about, but also with respect to the underlying concepts in use. This book offers a useful toolbox to approach this complex and fragmented field. It provides a biological access to the discussion using a 'layer' model that describes the connectivity of synthetic or semisynthetic organisms and cells to the realm of natural organisms derived by evolution. Instead of directly reviewing the field as a whole, firstly our book addresses the characteristic features of synthetic biology that are relevant to the societal discussion. Some of these features apply only to parts of synthetic biology, whereas others are relevant to synthetic biology as a whole. In the next step, these new features are evaluated with respect to the different areas of synthetic biology. Do we have the right words and categories to talk about these new features? In the third step, traditional concepts like "life" and "artificiality" are scrutinized with regard to their discriminatory power. This approach may help to differentiate the discussion on synthetic biology. Lastly our refined view is utilized for societal evaluation. We have investigated the public views and attitudes to synthetic biology. It also includes the analysis of ethical, risk and legal questions, posed by present and future practices of synthetic biology. This book contains the results of an interdisciplinary research projectand presents the authors' main findings and recommendations. They are addressed to science, industry, politics and the general public interested in this upcoming field of biotechnology.